Multicentre evaluation of a selective isolation protocol for detection of mcr‐positive E. coli and Salmonella spp. in food‐producing animals and meat. (21st April 2022) - Perrin‐Guyomard, Agnès; Granier, Sophie A.; Slettemeås, Jannice Schau; Anjum, Muna; Randall, Luke; AbuOun, Manal; Pauly, Natalie; Irrgang, Alexandra; Hammerl, Jens Andre; Kjeldgaard, Jette Sejer; Hammerum, Anette; Franco, Alessia; et al.
Abstract: This study was conducted to evaluate the performance of a screening protocol to detect and isolate mcr ‐positive Escherichia coli and Salmonella spp. from animal caecal content and meat samples. We used a multicentre approach involving 12 laboratories from nine European countries. All participants applied the same methodology combining a multiplex PCR performed on DNA extracted from a pre‐enrichment step, followed by a selective culture step on three commercially available chromogenic agar plates. The test panel was composed of two negative samples and four samples artificially contaminated with E. coli and Salmonella spp. respectively harbouring mcr ‐ 1 or mcr ‐ 3 and mcr‐4 or mcr ‐ 5 genes. PCR screening resulted in a specificity of 100% and a sensitivity of 83%. Sensitivity of each agar medium to detect mcr ‐positive colistin‐resistant E. coli or Salmonella spp. strains was 86% for CHROMID ® Colistin R, 75% for CHROMagar TM COL‐ APSE and 70% for COLISTIGRAM. This combined method was effective to detect and isolate most of the E. coli or Salmonella spp. strains harbouring different mcr genes from food‐producing animals and food products and might thus be used as a harmonized protocol for the screening of mcr genes in food‐producing animals and food products in Europe. Abstract : Significance and impact of the study: We performed a multicentre study to evaluate a protocol for the detection of mcr ‐carrying isolates combining selective pre‐enrichment, PCR and cultivation on commercial chromogenic selective agars. Adding a multiplex PCR step to detect mcr genes after the pre‐enrichment step can both save time and reduce costs by discarding negative samples. The performance of the method was influenced by the selective agar used and by the mcr variants to be detected. We propose a robust protocol that could be used in the frame of a harmonized European screening of mcr ‐positive E. coli and Salmonella spp. in food‐producing animals and food products.